Students’ Interests Becoming a Teacher through Kampus Mengajar MBKM Program - Meriza Armelita; Merie Agustiani; Shofiyatul Huriyah (JOLE (Journal of Language Education), 2024)
This research aims to find out Students’ Interest in Becoming A Teacher through Kampus Mengajar MBKM Program. This research was descriptive quantitative, with survey design method. The total sampling was used in this research which consisted of 56 students in Teacher Training and Education Faculty who have participated in the Kampus Mengajar Program Batch 4, 5, and 6. The data was collected through the questionnaire using Google Forms as an intermediary application. The research results showed that interest in becoming a teacher through Kampus Mengajar program was in the high category, with a percentage of 82%. This is viewed from the Affection aspect with a high interest category, and the Conation aspect in the high category. So it can be concluded that students at the Faculty of Teacher Training and Education at Baturaja University have a high interest in becoming teachers after participating in the Kampus Mengajar Program.